Sistem Informasi Pengelolaan Sertifikasi ISO pada PT NQA Indonesia Berbasis Web - Rekawaningtyas, Syifa Januarina; Fauziyah, Fauziyah; Whendasmoro, Raditya Galih (Universitas Muria Kudus, 2023)
PT NQA (National Quality Assurance) Indonesia is a company that operates in the field of ISO (International Standard Organization) standard certification. ISO certification is a conformity assessment procedure carried out to provide a written guarantee that a company or organization is declared to have met the standards set by ISO. In the PT NQA Indonesia ISO certification management process, it is difficult for clients to find information related to certification management documents, such as certification approval, certification schedule, and status, up to certificate delivery. Based on these conditions, this research aims to design and create an ISO certification management information system at PT NQA Indonesia. The system development stages in creating this information system use methods consisting of observation, interviews, literature study, system planning, or SDLC (System Development Life Cycle), running system analysis, system design and creation, black box testing, and using the MySQL programming language. With this information system, it is hoped to help the existing organizational structure at PT NQA Indonesia in carrying out the ISO certification management process and monitoring the certification management process for clients.